Fuels, energy, and the environment - Karim, G. A. (Boca Raton, FL : Taylor & Francis, 2013)
"Developed specifically for mechanical chemical, and petroleum engineering students, this book provides an up-to-date, informed, well-integrated, and balanced overview of the field of fuels science and technology with particular reference to energy supplies, efficiency, and the environment. It is an integrated yet simplified and concise presentation of the factors and processes that control the suitability of various types of fuels in combustion systems and their impact on the environment. This approach also links supportively with related conventional engineering courses such as thermodynamics, combustion, environmental engineering, chemistry, and materials"--
Fakulti Sains Bumi.
Includes bibliographical references and index.
Keywords: Energy conservation; Renewable energy sources